2012
DOI: 10.1016/j.yexcr.2012.06.022
|View full text |Cite
|
Sign up to set email alerts
|

The modulation of canine mesenchymal stem cells by nano-topographic cues

Abstract: Mesenchymal stem cells (MSCs) represent a promising cellular therapeutic for the treatment of a variety of disorders. On transplantation, MSCs interact with diverse extracellular matrices (ECMs) that vary dramatically in topographic feature type, size and surface order. In order to investigate the impact of these topographic cues, surfaces were fabricated with either isotropically ordered holes or anisotropically ordered ridges and grooves. To simulate the biologically relevant nano through micron size scale, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Similarly, rat [27] and canine MSCs [59] showed increased alignment and higher aspect ratio on channel patterned surfaces. Human BMSCs have been also tested on channels (pitch length 1.4-4 μm) [60] .…”
Section: Morphology Changes Of Adscs On Micropatterned Filmsmentioning
confidence: 90%
“…Similarly, rat [27] and canine MSCs [59] showed increased alignment and higher aspect ratio on channel patterned surfaces. Human BMSCs have been also tested on channels (pitch length 1.4-4 μm) [60] .…”
Section: Morphology Changes Of Adscs On Micropatterned Filmsmentioning
confidence: 90%
“…It should be noted that stiffness usually works in a cell-and material-specific manner because no difference in hMSC proliferation is found between the stiff and soft gelatin hydroxyphenylpropionic acid hydrogels [40], or even neural stem or progenitor cells prefer to proliferate on the soft methacrylamide chitosan substrate [41]. Moreover, substrate dimension also plays a potential role in stem cell proliferation, as observed by the proliferation rate of canine MSCs being significantly higher on 2-mm ridge and groove surfaces than that on 0.4-, 0.8-, 1.2-, 1.6-, and 4-mm surfaces [42], or by the rMSCs tending to proliferate on microhilled chitosan with a diameter of 5e30 mm but not 10 mm [43]. Our data also indicated that substrate dimension is more critical than its topography in this regard (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs have a profound regenerative ability attributed, in part, to their ability to modulate both the innate and adaptive immune systems [5][6][7]. Although the mechanisms of immunomodulation remain partially elusive, MSCs inhibit T-cell proliferation, alter B-cell function, downregulate major histocompatibility complex (MHC) II, and inhibit dendritic cell maturation and differentiation [6,[8][9][10]. Because of these functions, MSCs are currently in phase I-III human clinical trials for immunemediated diseases, including inflammatory alimentary tract diseases with promising results [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%